Faktor-Faktor yang Mempengaruhi Sikap Konsumen Memilih Masuk pada Lembaga Bimbingan Belajar di Kota Padang - Mayasari Mayasari; Rosmiati Rosmiati; Siti Syuhada; Refnida Refnida (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine and analyze the influence of factors that: influence consumer attitudes in choosing to enter a tutoring institution in the city of Padang in terms of potential factors, decision factors, partial and simultaneous consumer satisfaction value factors on consumer attitudes. The research method used is descriptive quantitative with a population of 20738 students who become consumers at tutoring institutions in the city of Padang. The sampling technique used is the Probability Random Sampling technique so that the sample of this study amounted to 392 people. The data were analyzed in two ways, namely: 1) using multiple linear regression to determine the factors that influence consumer attitudes with t and F tests at a significance level of = 0.05; 2) The attitude model of consumers choosing to enter a tutoring institution in Padang City is predicted based on the attitude toward the object model or the Fishbein model. The results showed that partially the institutional potential factors had a positive influence, the purchasing decision factor had a positive influence and the consumer satisfaction value factor had a significant negative influence on the attitudes of consumers choosing to enter a tutoring institution in the city of Padang. Meanwhile, simultaneously these factors have a significant influence on consumer attitudes in choosing tutoring institutions in the city of Padang. The consumer attitude model based on the Fishbein model choosing to enter a tutoring institution in the city of Padang has an average score of 32.62. This means that the tutoring institution in the city of Padang has the attributes that consumers want.